Diseño de un programa de seguridad y salud ocupacional para el aserradero “Kaliman 2” de la ciudad de Quevedo, año 2016 - Rivera Morante, Cristhian David (2016)
Any company that has in its area of more than 15 workers have the responsibility and legal obligation to take care in protecting all workers, including the safety of these against accidents and occupational diseases. These actions are integrated into the program of occupational health and safety, which includes the probabilistic method which calculate the degree of danger each risk that will be identified in this research. To identify risks that present themselves during the investigation we worked with GTC matrix 45, which is a matrix that allows identify, analyze and evaluate the risks presented during the investigation. With this continuous improvement of the entire work environment is sought with the aim of identifying the risks presented to take corrective measures proposed in the program of occupational health and safety proposals for the Sawmill "KALIMAN 2" It is for this reason that the program of occupational health and safety proposed for the Sawmill is vitally important for them as it improves the working environment and safety of all workers especially because the owner is obliged to provide security for all of them.